Scrutinizing Civil Servants Integrity in The Midst of Covid-19 Pandemic: A Netnographic Method - Ahmad Husni Hamim; Vidia Ayundhari (JPSI (Journal of Public Sector Innovations), 2021)
ABSTRACTIntegrity is one competency that civil servants must have. In this Covid-19 pandemic, civil servants integrity becomes an observable focus. The Work from Home (WFH) system may highly change the way how they work at home. The research aims at scrutinizing integrity inferences of civil servants during the pandemic. WhatsApp, as an application used by them to communicate, has become a significant medium to observe the patterns. Netnography method is used to observe civil servants community behavior on social media. From the inferences observation, it is discovered that they have demonstrated forms of integrity, such as responsibility and professionalism. The civil servants are also getting more solid, helping, and relying on each other. When conflict occurs, they will retain the right principle. On the other hand, some would balance the situation. Consistency and discipline sensed from how civil servants perceiving all-online-formats. To sum up, performing online duties during Work from Home (WFH) has shown forms of integrity among civil servants. ABSTRAKIntegritas merupakan salah satu kompetensi yang harus dimiliki seorang ASN. Dalam situasi pandemi Covid-19, integritas ASN menjadi sebuah fokus yang patut diobservasi. Sistem Work from Home (WFH) mau tidak mau mengubah cara kerja seorang ASN ketika berada di rumah. Tujuan dari penelitian ini untuk mengamati inferensi integritas ASN selama pandemi. WhatsApp, sebagai aplikasi yang digunakan para ASN untuk berkomunikasi menjadi media yang signifikan dalam mengamati pola-pola integritas tersebut. Metode netnografi digunakan untuk mengamati perilaku komunitas ASN pada media sosial. Dalam pengamatan inferensinya, ditemukan bahwa ASN telah menunjukkan bentuk-bentuk integritas seperti, tanggungjawab dan profesionalisme. Para ASN juga semakin solid, saling membantu, dan mengandalkan satu sama lain. Setiap sebuah konflik terjadi, mereka akan mempertahankan prinsip yang benar. Di sisi lain, ada yang menyeimbangkan situasi. Konsistensi dan kedisiplinan juga terlihat dari bagaimana ASN memandang format serba daring. Dapat disimpulkan bahwa performa dalam menyelesaikan tugas-tugas daring menunjukkan berbagai bentuk integritas para ASN.